2018
DOI: 10.1093/jas/sky174
|View full text |Cite
|
Sign up to set email alerts
|

The combined effects of supplementing monensin and 3-nitrooxypropanol on methane emissions, growth rate, and feed conversion efficiency in beef cattle fed high-forage and high-grain diets1

Abstract: The study objective was to evaluate the combined effects of supplementing monensin (MON) and the methane (CH4) inhibitor 3-nitrooxypropanol (NOP) on enteric CH4 emissions, growth rate, and feed conversion efficiency of backgrounding and finishing beef cattle. Two hundred and forty crossbred steers were used in a 238-d feeding study and fed a backgrounding diet for the first 105 d (backgrounding phase), transition diets for 28 d, followed by a finishing diet for 105 d (finishing phase). Treatments were as follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
87
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(96 citation statements)
references
References 49 publications
7
87
1
1
Order By: Relevance
“…The 70% reduction in CH 4 emissions due to 3‐NOP (125 mg kg −1 DM daily) was greater than the 12% (100 mg kg −1 DM daily; Vyas et al, 2018) and 41% (125 mg kg −1 DM daily; Vyas et al, 2018) reduction reported previously with beef cattle fed high grain diets containing 3‐NOP. Those studies measured CH 4 emissions using whole‐animal chambers.…”
Section: Resultsmentioning
confidence: 61%
“…The 70% reduction in CH 4 emissions due to 3‐NOP (125 mg kg −1 DM daily) was greater than the 12% (100 mg kg −1 DM daily; Vyas et al, 2018) and 41% (125 mg kg −1 DM daily; Vyas et al, 2018) reduction reported previously with beef cattle fed high grain diets containing 3‐NOP. Those studies measured CH 4 emissions using whole‐animal chambers.…”
Section: Resultsmentioning
confidence: 61%
“…2019R1F1A1056904). ments methods of CH 4 emissions among all used studies [12][13][14][15][16][17][18][19][20][21][22][23][24][25] (Table 1). In short, the administration methods of NOP were direct administration via cannula, top dressed, and mixed with diet.…”
Section: Funding Sourcesmentioning
confidence: 99%
“…The most important factor in investigating an effective CH 4 mitigation strategy in rumen is persistent efficacy. With our knowledge, total 5 in vivo studies were conducted to investigate the effects of NOP supplementation on sustained mitigation of CH 4 emission [15,16,19,22,25]. Romero-Perez et al [19], conducted a long-term study where eight ruminally cannulated heifers were fed a TMR, with a 60% forage ratio, supplemented with NOP (2 g/d of NOP) for about 146 d. Methane emissions were reduced up to 59% for both the g/d and g/kg of DMI in the NOP supplemented groups.…”
Section: Methane Mitigationmentioning
confidence: 99%
See 2 more Smart Citations